In vitro and in silico Evaluation of Some Natural Molecules as Potent Glutathione Reductase Inhibitors - Tuba Aydin (International Journal of Secondary Metabolite, 2020)
Glutathione reductase inhibitors are very popular antimalarial and anticancer agents. In this study, in vitro inhibition effects of β-sitosterol, stigmasterol, diosgenin and jervine which containing steroidal structure were determined against glutathione reductase enzyme. β-sitosterol, diosgenin and jervine were isolated from Veratrum album and stigmasterol was isolated from Artemisia dracunculus L. by chromatographic methods. According to the results obtained, IC50 values of β-sitosterol, stigmasterol, diosgenin and jervine were found as 1.2580, 5.2116, 0.1916 and 0.7701 µM, respectively. Among test compounds, diosgenin showed the strongest inhibitory effect against glutathione reductase with Swissdock docking figure. In current study first time, β-sitosterol, stigmasterol, diosgenin and jervine were found to be much more glutathione reductase inhibitors.